Keterampilan Komunikasi Kepemimpinan Chief Pilot (Studi Kasus Chief Pilot Airbus 330-300 Garuda Indonesia) - Lisa Novianti; Rosmawaty Hilderiah Pandjaitan (Universitas Mercu Buana, 2018)
Abstract This research is motivated by several cases in Pilot PT. Garuda Indonesia, Tbk. (PT GI) ranging from cases of strikes to violations of law and ethics. Though there is already Chief Pilot assigned to communicate and control their performance through leadership communication. But in fact, there are still many obstacles. That is why researchers interested want to know, reveal, and unravel about leadership communication skills of Chief Pilot in controlling the performance of Pilot PT. Garuda Indonesia, Tbk, especially on Airbus 330-300 Chief Pilot, because the Airbus 330-300 Pilots are numerous, and also spread all over the world. The objective is to generate an understanding of the Chief Pilot leadership form, motives, and obstacles in controlling the performance of the Pilot PT. Garuda Indonesia, Tbk. The theory used is Organizational Control Theory and Situational Leadership Theory, in Constructivist paradigm, and a descriptive case study perspective. The results of this study can be understood that the form of leadership skills of Chief Pilot leadership skills are effective listening skills, verbal and non verbal skills, trust building skills, skills to improve understanding, empowering others skills, technical control skills, and bureaucratic control skills. The Chief Pilot's leadership communication motive is to connect, to convince, to provide a complex arrangement of situations, to control pilot behavior, to be a spokesman, and to monitor pilot quality. The obstacles of Chief Pilot leadership communication skills are, physical obstacles, psychosocial barriers, and distance barriers. Keywords: Communication Skills, Leadership, Pilot